Cardiovascular therapeutics a companion to Braunwald's heart disease - Antman, Elliott M; Sabatine, Marc S. (Elsevier/Saunders, 2013)
This companion to Braunwald's Heart Disease equips you with all of today's most effective therapeutic guidelines and management solutions for the full range of heart disease patients. It reflects the most recent standards for drug management as well as the latest in new technologies. Reorganized to mirror your changing practice, each cardiovascular-problem-based section offers a chapter on pharmacologic treatment (with a minimum of pathophysiology)...a chapter on catheter-based or minimally invasive interventions...and a discussion of surgical options. You'll also find a brand-new chapter on gene therapy and stem cell therapy, plus new chapters on many other rapidly developing areas of practice. The result is an outstanding single-volume source for state-of-the-art, clinically oriented guidance on both common and unusual areas of cardiovascular treatment.